Natural Film Based on Pectin and Allantoin for Wound Healing: Obtaining, Characterization, and Rat Model - Meza-Valle, Karen Zulema; Saucedo Acuña, Rosa Alicia; Rios Arana, Judith Virginia; Lobo Galo, Naun; Cuevas-González, Juan Carlos; Tovar Carrillo, Karla Lizette; Rodriguez, Carlos (2020)
Introduction. In our days, several approaches reported the use of natural compounds in medical applications. Among them, pectin and allantoin are nontoxic, biocompatible, and biodegradable; however, its use for possible wound healing therapeutics is still limited. Pectin and allantoin have been applied in pharmaceutical industry and beauty cosmetic and could be also applied as scaffolds for tissue regeneration, wound healing, and so on. The aim of this study was to combine by the first time two natural ingredients to develop a new biomaterial to treat skin injuries in a rat model. Methods. For the hydrogel development, new synthesis parameters were established for the obtaining of the film such as temperature, mixing velocity and time, and drying temperatures as well. To enrich the film, the allantoin concentrations were set at 90 wt% and 100 wt% of pectin used. By in vivo assay, films were tested in wound healing in female Wistar rats, 190 ± 10 g in weight and 2 months aged. Results. The obtained films comprise 2 well-differentiated layers, one layer rich in allantoin, which will be the regenerative layer, and one rich in pectin, which will work as an antimicrobial and protective layer to the wound. These were characterized by swelling kinetics, Fourier transform of the infrared spectrum of absorption (FTIR) spectroscopy, and contact angle. The morphology and topography were determined by scanning electron microscopy (SEM) and confocal laser scanning microscopy (CLSM). In vivo assay showed remarkable reduce in a time period in a wound healing process when the film was used. The results show that the use of PA (Pectin-Allantoin) hydrogel reduces the total healing time by 25% approximately. Conclusions. Pectin-Allantoin (PA) film has potential use in medical applications as wound healing material promoting healthy tissue renewal.